2018
DOI: 10.1108/jiabr-01-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

WhetherShari’ahcompliance efficiency is a matter for the financial performance

Abstract: Purpose Shari’ah is the foundation of Islamic banks. Although all the Islamic banks required complying with the Shari’ah requirements fully, the level of compliance differs among the Islamic banks. At the same time, Islamic banks have been performing well, but all do not demonstrate similar financial performance. This paper aims to explore whether Shari’ah compliance efficiency makes any difference in financial performance of Islami Bank Bangladesh Limited (IBBL). Design/methodology/approach This study used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 31 publications
0
46
0
3
Order By: Relevance
“…It also indicates that sharia compliance is not the main factor determining the performance of Islamic banks. Although according to (M. H. Ullah & Khanam, 2018) sharia is the basic principle that should direct all the activities of Islamic banks the research findings show that sharia compliance does not significantly affect the financial performance of Islamic banks.…”
Section: Sharia Compliance and Bank Performancementioning
confidence: 82%
“…It also indicates that sharia compliance is not the main factor determining the performance of Islamic banks. Although according to (M. H. Ullah & Khanam, 2018) sharia is the basic principle that should direct all the activities of Islamic banks the research findings show that sharia compliance does not significantly affect the financial performance of Islamic banks.…”
Section: Sharia Compliance and Bank Performancementioning
confidence: 82%
“…However, social performance does not always impact negatively on the financial performance of Islamic banks. For instance, Ullah Md and Khanam (2018) illustrate that Sharī'ah compliance can lead IBs to achieve higher financial positions. They show that more Sharī'ah compliance and social work can attract more funds, satisfied employees, new clients, other stakeholders, and consequently improved performance in financial indicators.…”
Section: Resultsmentioning
confidence: 99%
“…In a case study of Islami Bank Bangladesh Limited (IBBL), Ullah and Khanam (2018) found that the favourable financial performance of IBBL was largely driven by Shariah compliance. Not all Islamic banks in Bangladesh comply with Shariah law, however.…”
Section: Current Practice Of Shariah Governance In Bangladeshmentioning
confidence: 99%